Efektivitas Massage untuk Meningkatkan Produksi Air Susu Ibu (ASI) pada Ibu Postpartum - Kartini, Monica; Kusumadewi, Berlian Nurtyashesti (STIKES Ngesti Waluyo, 2023)
Giving breast milk in the first two years of a baby's life improves the health, growth, development and intelligence of children, and provides protection against various diseases. However, various obstacles are often encountered, both from the mother's side and the less optimal role of health workers in providing care for postpartum mothers, so that the target of early and exclusive breastfeeding for babies has not been achieved. This study aims to identify, evaluate and synthesize literature on massage methods and their effect on breast milk production and postpartum depression. Using the literature review method, research articles were searched in the Pubmed and GARUDA databases for articles published in 2013-2023 using keywords: massage, milk production, breast milk, breastfeeding, postpartum. The initial search results found 122 articles, and after checking and appraisal, there were 22 relevant articles for review. There are various types of massage methods for postpartum mothers that are effective for increasing milk production, and the most widely practiced is oxytocin massage, either just oxytocin massage or in combination with other techniques such as acupressure, marmet massage, oketani massage, music therapy or massage using lavender essential oil. Massage performed on postpartum mothers will make mothers feel comfortable, reduce depression and pain sensations, make the body more relaxed, reduce stress hormones, increase the level of hormones prolactin and oxytocin, and increase milk production. Massage that is done twice a day (morning and evening) with a duration of 10-15 minutes or 30-60 minutes for 3-14 days is effective for increasing the production of breast milk in postpartum mothers and reducing depression.